2021
DOI: 10.1021/acs.biomac.1c00134
|View full text |Cite
|
Sign up to set email alerts
|

CO2-Triggered ON/OFF Wettability Switching on Bioinspired Polylactic Acid Porous Films for Controllable Bioadhesion

Abstract: Bioinspired honeycomb-like porous films with switchable properties have drawn much attention recently owing to their potential application in scenarios in which the conversion between two opposite properties is required. Herein, the CO 2 -gastriggered ON/OFF switching wettability of biocompatible polylactic acid (PLA) honeycomb porous films is fabricated. Highly ordered porous films with diameters between 2.0 and 2.8 μm are separately prepared from complexes of nonresponsive PLA and a CO 2 -sensitive melamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Since the first report of condensing droplets by Lord Rayleigh in 1911, 17 the BF method uses volatile solvents to induce vapor condensation, leaving porous imprints after the total evaporation of solvents and droplets. The stability of water droplets and their rearrangement by Marangoni convection and thermocapillary force ensure the formation of honeycomb patterns 18–31 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first report of condensing droplets by Lord Rayleigh in 1911, 17 the BF method uses volatile solvents to induce vapor condensation, leaving porous imprints after the total evaporation of solvents and droplets. The stability of water droplets and their rearrangement by Marangoni convection and thermocapillary force ensure the formation of honeycomb patterns 18–31 …”
Section: Introductionmentioning
confidence: 99%
“…The stability of water droplets and their rearrangement by Marangoni convection and thermocapillary force ensure the formation of honeycomb patterns. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] Up to now, a lot of polymers with different topological structures have been investigated in the BF process, including star-shaped polymers, 18,32,33 dendrimers, 34 comb-like polymers, 35 rod-coil block copolymers, 36,37 and linear polymers. [38][39][40][41][42][43] Apart from topology, the chemical composition of polymers also shows great impact on their self-assembly behavior.…”
mentioning
confidence: 99%
“…Highly-ordered patterned porous films mimicking natural honeycomb structures have attracted much research interest because of their ordered porosity, lightweight, stretchability, mechanical strength, and high surface area [ 1 , 2 , 3 ]. These properties make them highly desirable for potential applications such as antibacterial membranes [ 4 , 5 ], microelectronics [ 6 ], sensors [ 7 , 8 , 9 , 10 , 11 ], cell culture scaffolds [ 12 , 13 ], superhydrophobic surfaces [ 14 , 15 ], and size-selective separators [ 16 ]. These films can be obtained either via top-down lithographic techniques, such as photo-lithography [ 17 ] and contact lithography, or bottom-up fabrication such as self-assembly mechanisms of colloidal particles [ 18 , 19 ], emulsions [ 20 , 21 ], block copolymers [ 22 , 23 ], and phase separation [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 31 ] Furthermore, some research groups have reported that HCF has potential as a promising cell culture scaffold. [ 32–35 ]…”
Section: Introductionmentioning
confidence: 99%